Edukasi Manajemen Keperawatan dalam Kondisi Bencana Darurat pada Siswa (i) di SMA Bawakaraeng - Rusli Abdullah; Ricky. Z; Abd. Herman Syah Thalib; Fatmawati Fatmawati; Annisa Salsabila (Jurnal DIKMAS, 2021)
Preparedness is the key to safety. This shows that there is a need for an earthquake and tsunami disaster preparedness plan so that losses can be minimized. Earthquake and Tsunami Disaster Preparedness education was provided on November 18 2021 at Bawakaraeng High School. The aim of this service is to provide education on earthquake and tsunami disaster preparedness provided by Lecturers and Students of the D3 Nursing Study Program, Makassar College of Health Sciences, which can provide benefits and refresh the knowledge of Bawakaraeng High School children in dealing with earthquake and tsunami disasters. The method used was lecture and question and answer with 50 participants (i) level II (Class XI). The results of the activity showed that there was an increase in knowledge after the education was carried out, namely 96%, so it is hoped that when an emergency disaster occurs students will be ready and understand the things that must be done.